Relationship between Heart Failure Treatment and Self-Management Compliance in Congestive Heart Failure Patients - Ariwati Anggita Putri; Dian Hudiyawati (Universitas Muhammadiyah Surakarta, 2022)
Self-management has a vital role in treating Congestive Heart Failure (CHF) patients to manage themselves and maintain the ability of body functions. Self-management can be seen in how heart failure patients perform compliance actions in treatment and the patient's ability to know changes in behaviour towards the patient's health status. In addition, it is crucial for people with congestive heart failure to learn about their disease to relieve the signs and symptoms. This study aimed to determine the relationship between knowledge of heart failure care and self-management compliance in CHF patients. This method uses a quantitative correlation research type to determine the relationship between the two variables using an analytical cross-sectional study approach. The sampling technique uses accidental sampling from March to April 2021 at the heart poly Hospital of UNS Surakarta to 100 respondents. Sample criteria: Respondents with a diagnosis of CHF who checked their health at the heart polyclinic of UNS Surakarta Hospital, aged 17 years, patients with NYHA classification 1-3, and willing to be respondents. The research instrument used a demographic questionnaire, knowledge of heart failure care and the Self Care Heart Failure Index (SCHFI) to determine the self-care knowledge of CHF patients and adherence to self-management. The results obtained through the chi-square test showed a p-value of 0.010, meaning there is a relationship between knowledge of heart failure care and self-management compliance. Knowledge of heart failure care can affect the level of compliance of CHF patients because CHF patients need self-management compliance to minimize symptoms of recurrence or worsening of signs and symptoms and reduce the impact of re-hospitalization.